Search 75,787 tutors
0 0

## (8m7c9)(3m9c7)

Where do I begin to solve this?

Please clarify the format of this problem, is it [8(m^7)(c^9)][3(m^9)(c^7)]?

It seems like numbers are exponents , you should write as Superscript or use( ^ ) , m6 is written normally as 6m.

(8 m7 c 9 ) ( 3 m9c7) = 24 m16 c16  / multiplication of exponent with the same base, same base with
exponent as sum.

Break up one factor into individual factors and then multiply, as follows:

(8m7c9)(3m9c7) = (8m7c9)(3)(m)(9)(c)(7)

= {(8m7c9)(3)} (m)(9)(c)(7)

Note that (8m7c9)(3) = (8m7c9)+(8m7c9)+(8m7c9)
= (24m7c9)

Similarly (24m7c9)(m) = (24m7c9) + (24m7c9) + ...m times
= (24(m^2)7c9)

Continuing gives (8m7c9)(3m9c7)= 24*(m^2)*63*(c^2)*63
=24*63*63*(m^2)*(c^2)

= 95256*(m^2)*(c^2)

Note that if the first term (8m7c9) were the sum (8+m+7+c+9) then the indivdual factors of (3m9c7) would be distributed among each item in (8+m+7+c+9), ie

(8+m+7+c+9)*3 would equal (24+3m+21+3c+27) ... and so forth for the other factors of (3m9c7).
BDS